2021
DOI: 10.22159/ijap.2021.v13s3.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antihyperglycemic Activity of Different Parts of Klutuk Banana (Musa Balbisiana Colla)

Abstract: Objective: Banana is a plant that grows in Indonesia and is widely consumed by Indonesian people. One of banana type is klutuk banana (Musa balbisiana Colla). There were many types of researches about klutuk banana for antidiabetic activity; however, antidiabetic activity of its peel and pulp are still unknown. Methods: The objective of the study was to determine of antihyperglycemic activity of different parts of klutuk banana. Animals were divided into 15 groups, namely normal control, negative control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies reported that the banana peel is rich in chemical compounds as antioxidant and antimicrobial activities [ 167 , 168 , 169 , 171 ]. Moreover, ethanoic extract from banana peel exhibited the strongest antihyperglycemic activity in comparison with the extract from pulp, seed, and flower [ 172 ]. Phytochemicals derived from banana peel were tested as a biofungicide against Fusarium culmorum and Rhizoctonia solani and as a bactericide against Agrobacterium tumefaciens for the natural preservation of wood during handling or in service.…”
Section: Phytochemicals From Crop Residuesmentioning
confidence: 99%
“…Previous studies reported that the banana peel is rich in chemical compounds as antioxidant and antimicrobial activities [ 167 , 168 , 169 , 171 ]. Moreover, ethanoic extract from banana peel exhibited the strongest antihyperglycemic activity in comparison with the extract from pulp, seed, and flower [ 172 ]. Phytochemicals derived from banana peel were tested as a biofungicide against Fusarium culmorum and Rhizoctonia solani and as a bactericide against Agrobacterium tumefaciens for the natural preservation of wood during handling or in service.…”
Section: Phytochemicals From Crop Residuesmentioning
confidence: 99%